Numerical simulation of oxy-coal MILD combustion with high-velocity oxygen jets. Issue 1 (February 2017) - Liu, Ruochen; An, Enke; Wu, Kun; Liu, Zeqing
Abstract: For achieving efficient oxy-coal combustion in a MILD state, the optimum operating conditions with high-velocity jets in a lab-scale cylindrical furnace was determined. The flow characteristics, combustion temperature, ignition characteristics, emissions under different oxygen jet design and jet spacing were simulated and compared. The results show that the ignition temperature is 517 °C for Datong bituminous coal with an averaged particle size of 60 um; the ignition delay is approximately 10–15 ms under co-flow jets conditions and only 4 ms under coaxial jets condition. Under co-flow jets conditions, except for the case L = 75 mm, as the jet spacing increases, the oxidizer flow could be internally diluted to a lower concentration and preheated to a higher temperature, at least 1200 K. The maximum temperature increase in furnace is approximately 915 °C for L = 75 mm and 880 °C for coaxial jets, both are not MILD combustion. Co-flow jets with L = 30–60 mm are recommended, taking L = 30 mm condition as example, the combustion temperature fluctuated no more than 15%, and almost no CO and 50–70 ppm NO emission exist in the outlet of the furnace. Highlights: In this work, oxy-coal combustion and MILD combustion are combined based on high-velocity oxygen entrainment technology, which is a new concept for combustion. It differs from air-firing due to high concentration of CO2 as well as oxy-coal combustion due to its distributed combustion mode. The flow characteristics, combustion temperature, ignition characteristics, emissions under different jet design and jet spacing were compared in a lab-scale cylindrical furnace. So far, MILD combustion state is judged qualitatively, while a mathematical method corresponding to internally mixing and preheating zone was introduced here to judge MILD combustion state through numerical simulation. It based on the MILD combustion definition. These numerical simulation work lays foundation for the further experiments, having referencing value to a large degree.